Datasets for quantifying association between short-term exposure to maximum temperature and heatstroke-related ambulance dispatches in Japan: A time-stratified case-crossover designZenodo - Keita Wagatsuma (Data in Brief)
This study provides a comprehensive collection of open-access daily time-series datasets designed to quantify the association between short-term exposure to maximum temperature and heatstroke-related ambulance dispatches (HSAD) utilizing a two-stage time-stratified case-crossover design. The datasets include daily records of HSAD, maximum temperature (°C), and relative humidity (%) for the summer months (i.e., June to September) from 2015 to 2019, spanning all 47 Japanese prefectures and covering the entire country. These datasets are well-suited for time-series regression analyses to estimate location-specific maximum temperature-HSAD associations in Japan. The availability of data from multiple locations also facilitates the of regional differences by aggregating location-specific associations within broader geographical areas. This resource is intended to support researchers, educators, and students in leveraging time-series analysis for research and educational purposes.